2020
DOI: 10.1016/j.jvs.2019.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal open abdominal aortic aneurysm repair is associated with higher rates of late reintervention and readmission compared with the retroperitoneal approach

Abstract: Objective: Limited data exist comparing the transabdominal and retroperitoneal approaches to open abdominal aortic aneurysm (AAA) repair, especially late mortality and laparotomy-related reinterventions and readmissions. Therefore, we compared long-term rates of mortality, reintervention, and readmission after open AAA repair through a transabdominal compared with a retroperitoneal approach. Methods: We identified all patients in the Vascular Quality Initiative (VQI) undergoing open AAA repair from 2003 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The use of mesh reinforcement reduced this risk to 16% (P < .004). Also, we believe that the rate of incisional hernias is much higher than the 13% noted in the study reported by Deery et al 1 Moreover, the retroperitoneal approach through an oblique incision can result in two different complications. It could result in a true hernia but could also result in a bulge, which is a myofascial laxity without defects.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…The use of mesh reinforcement reduced this risk to 16% (P < .004). Also, we believe that the rate of incisional hernias is much higher than the 13% noted in the study reported by Deery et al 1 Moreover, the retroperitoneal approach through an oblique incision can result in two different complications. It could result in a true hernia but could also result in a bulge, which is a myofascial laxity without defects.…”
mentioning
confidence: 60%
“…We read with a great interest the article from Derry et al 1 In their study, the 5-year rate of laparotomy-related reinterventions was greater after the transabdominal approach than after the retroperitoneal approach (13% vs 6.1%). These results would, therefore, encourage favoring the retroperitoneal approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We appreciate your comments regarding our study evaluating outcomes after open abdominal aortic aneurysm (AAA) repair using a retroperitoneal vs transabdominal approach. 1 In our study of Medicare beneficiaries, patients who underwent transabdominal AAA repair had higher rates of repair-related readmissions and reinterventions compared with patients who underwent a retroperitoneal approach at 5 years (42% vs 34%), and this was driven primarily by higher rates of hernia repairs (13% vs 6.1%; P < .01). As suggested in the above letter, these numbers do not account for all hernias or abdominal wall bulges, but only those who ultimately underwent intervention.…”
Section: Replymentioning
confidence: 73%
“…With an open surgical approach, poorer outcomes occur with transabdominal access (which we used). 10 The reimplantation of the IMA was rejected because of the critical stenosis at the origin and a 2-mm diameter along the entire length.…”
Section: Discussionmentioning
confidence: 99%